(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
A Broom Graph Bn,d is a graph of n vertices, which have a path P with d vertices and (n-d) pendant vertices, all of these being adjacent to either the origin u or the terminus v of the path P. Here we consider various labeling on Broom graph such as Cordial labeling, Antimagic labeling and b-coloring.